PENERAPAN MODEL PEMBELAJARAN ROLE PLAYING (BERMAIN PERAN) UNTUK MENANAMKAN NILAI TOLERANSI PADA SISWA SD. - Setiani, Henny; Juhanah; Sari, Sindy Fatika; Afifah, Fitri Nur; Sukaesih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study evaluates the effectiveness of the role-playing learning model in instilling tolerance in elementary school students. Tolerance is a crucial value that needs to be developed from an early age to create harmony in a pluralistic society. Conventional learning methods are often ineffective in internalizing this value. Using a literature review approach, this study analyzed various scientific sources regarding the application of role-playing as an active learning method that provides students with direct experience in understanding and embracing tolerance. The results show that role-playing improves students' cognitive understanding and affective aspects—such as empathy, self-confidence, and social skills. The integration of local wisdom enriches the learning context, making the value of tolerance more relevant and meaningful. The role of teachers and a supportive school environment are crucial factors in successful implementation. In conclusion, the role-playing model is effective in developing character education at the elementary school level.